Report on Pilot innovations implemented and stakeholders' evaluations workshop - Wassie, Shimels Eshete; Ambaw, Gebermedihin; Baker, Derek; Wilkes, Andreas (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The half-day workshop session on Pilot innovations implemented and stakeholders' evaluations involved the participation of the following national directorates of Ethiopia's Ministry of Agriculture (MoA): CRGE; Milk Resource Development; Meat, Hide and Skin Development; Poultry Resource Development; Forage Resource Development; Animal Disease Prevention and Control; Livestock Identification, Traceability and Welfare; Export Slaughterhouse Inspection and Certification; as well as the World Bank Livestock and Dairy Development Program; the Oromia Forested Landscape Program; the Ethiopian Agricultural Research Institute (EIAR); the Agricultural Department of the Central Statistics Agency (CSA); the Environment, Forests and Climate Change Commission (EFCCC); the Food and Agriculture Organization (FAO) of the United Nations; the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS); UNIQUE forestry and land use GmbH; the US Forest Service; and the International Livestock Research Institute (ILRI); Intergovernmental Authority on Development (IGAD); Global Programs, Foreign Agricultural Service (USDA), Australian Centre for International Agricultural Research (ACIAR). The main objectives of the workshop are to discuss the result of the pilot tests with relevant stakeholders and to discuss the way forward on the implementation of pilots and support upscaled adoption of validated innovations to support the effective operation of an improved livestock MRV system in Ethiopia